FAMILY OCCUPATION AND ENTRENEURIAL MOTIVATION – A STUDY (International Journal of Food and Nutritional Sciences, 2022)
Motivation is the process that motivates a person into action and induces him to continue the courses of action for the achievement of goals. Ambitions or aspiration motivates men, activise them, broaden their vision and make the life meaningful. Ambition is an index of one’s own resourcefulness. The intentions and initiative of a man are directed by his ambitions. The common saying “aimless life is a goal less game” emphasizes the importance of ambition in life. Various ambitions which motivate a person to become an entrepreneur are need for independence, to make money, previous experience, unemployment, securing social status, availability of industrial shed or plot, fulfillment of father’s ambition etc.The paper focuses on factors motivating the entrepreneurs, the relationship between motivational factors and parental occupation. The paper is based on primary sources collected from 60 entrepreneurs running their units in KSSIDC industrial estates of Shivamogga district. The response is collected using structured interview schedule using stratified random sampling technique.The study finds that making money, the opportunity to start the unit/availability of KSSIDC shed, humble to become an employer, previous experience and need for independence, encouragement from friends/relatives, the unemployment problem, securing social status, fulfillment of father’s ambition and education/training in the related line, EDP and EAP participation and success stories of other entrepreneurs are the factors motivated the entrepreneurs in the order of importance.To see the degree of relationship between motivational factor and parental occupation, the chi-square test for each background is calculated. The calculations shown that, the calculated value is less than the table value. Therefore the null hypothesis that there is no significant relationship between parental occupation and motivational factor is accepted.